2019
DOI: 10.1038/s41598-019-42066-4
|View full text |Cite|
|
Sign up to set email alerts
|

When the statistical MMN meets the physical MMN

Abstract: How do listeners respond to prediction errors within patterned sequence of sounds? To answer this question we carried out a statistical learning study using electroencephalography (EEG). In a continuous auditory stream of sound triplets the deviations were either (a) statistical, in terms of transitional probability, (b) physical, due to a change in sound location (left or right speaker) or (c) a double deviants, i.e. a combination of the two. Statistical and physical deviants elicited a statistical mismatch n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…The effect consists of an attenuated N2 amplitude in pattern (vs. random) presentations, which has been also related to the deployment of more attentional resources. In the same latency range, Koelsch et al ( 2016 ) and Tsogli et al ( 2019 ) recently reported an analog of the mismatch negativity (MMN) wave, called the statistical MMN (sMMN), to index the automatic change detection processes based on implicit extraction of statistical regularities embedded in the input.…”
Section: Introductionmentioning
confidence: 99%
“…The effect consists of an attenuated N2 amplitude in pattern (vs. random) presentations, which has been also related to the deployment of more attentional resources. In the same latency range, Koelsch et al ( 2016 ) and Tsogli et al ( 2019 ) recently reported an analog of the mismatch negativity (MMN) wave, called the statistical MMN (sMMN), to index the automatic change detection processes based on implicit extraction of statistical regularities embedded in the input.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is the mismatch negativity, which is elicited by stimuli with a low probability of occurrence, even when presented outside the focus of attention (e.g. Koelsch et al, 2016; Tsogli et al, 2019). Using MEG, Paraskevopoulos et al (2012) demonstrated a mismatch response to part-triplets compared to triplets during exposure to a statistically regular stream, as early as 50ms after stimulus onset, even though participants’ post-exposure recognition was at chance level.…”
Section: Introductionmentioning
confidence: 99%
“…Koelsch and colleagues (2016) found that the amplitude of this response was negatively related to the probability of an auditory event. It has been suggested that this early component reflects the magnitude of prediction errors in statistical learning contexts (Tsogli, Jentschke, Daikoku, & Koelsch, 2019).…”
Section: Introductionmentioning
confidence: 99%